Isolated blunt pancreatic trauma: A benign injury?. Issue 5 (November 2016) - Siboni, Stefano; Kwon, Edward; Benjamin, Elizabeth; Inaba, Kenji; Demetriades, Demetrios
Abstract : BACKGROUND: Blunt pancreatic trauma is rare, and the reported mortality is high. The true outcomes in isolated pancreas trauma are not known, and the optimal management according to injury severity is controversial. The present study evaluated the incidence, outcomes, and optimal management of isolated blunt pancreatic injuries. METHODS: National Trauma Data Bank study, including patients with blunt pancreatic trauma. Patients with major associated injuries or other severe intra-abdominal injuries were excluded. Patients' demographics, vital signs on admission, Abbreviated Injury Scale for each body area, Injury Severity Score (ISS), and therapeutic modality were extracted. Mortality and hospital length of stay were stratified according to the severity of pancreatic injury and therapeutic modality. RESULTS: There were 388, 137 patients with blunt abdominal trauma. Overall, 12, 112 patients (3.1%) sustained pancreatic injury. Isolated pancreatic injury occurred in 2, 528 (0.7%) of all abdominal injuries or 20.9% of pancreatic injuries. Most injuries were low-grade Organ Injury Scale ((OIS) score of 2, 82.7%) with only a small percentage of higher-grade injuries (OIS score of 3, 7.9%; OIS score of 4, 3.9%; and OIS score of 5, 5.5%). Overall, most patients (74.1%) were managed nonoperatively. Nonoperative management was selected in 80.5% of pancreas OIS score of 2, 48.5% of OIS score of 3, and 40.9% of OIS scores of 4 to 5. The overall mortality rate was 2.4%, while in severe pancreatic trauma it was 3.0%. In minor pancreatic trauma, nonoperative management was associated with lower mortality and shorter hospital length of stay than operative management. However, in the group of patients with severe pancreatic trauma (OIS scores, 4–5) nonoperative management was associated with higher mortality and longer hospital stay than definitive operative management of the pancreas. CONCLUSIONS: The mortality in isolated pancreatic trauma is low, even in severe injuries. Nonoperative management of minor pancreatic injuries is associated with lower mortality and shorter hospital stay than operative management. However, in severe trauma, nonoperative management is associated with higher mortality and longer hospital stay than operative management. LEVEL OF EVIDENCE: Prognostic study, level III; therapeutic study, level IV.